Characterization of microorganisms present in a slaughterhouse and beef processing/chilling environment - Macedo, Neida Terezinha Souza; Van Der Sand, Sueli Teresinha (Acta Scientiae Veterinariae, 2018)
The ingestion of contaminated foods of animal origin has considerably increased the occurrence of food-borne diseases. Several bacterium species are deemed responsible for outbreaks of those diseases and the presence of such species in food processing plants depends on the proper hygiene routines there adopted. The aims of this study were: (i) to isolate and characterize the microorganisms present in a bovine slaughterhouse and processing/chilling environment, and (ii) to identify enterotoxigenic Escherihcia coli (ETEC) among isolates using the PCR amplification protocol. Out of the total 580 bacteria isolated and identified by biochemical assays, 168 were Staphylococcus aureus, 123 Escherichia coli, and 79 Corynebacterium vitarumem. The remaining belonged to the Bacillus spp. and Corynebacterium spp. genera, and to the Enterobacteriaceae family. The 123 bacteria identified as E. coli underwent a plasmid DNA extraction routine for the PCR assays. The results revealed 37 E. coli isolates to be positive for the ST gene, out of which 20 were correspondingly positive for the LT gene and 2 were only LT positive. The data evidenced the predominance of bacteria indicating faecal contamination and of bacteria found in bovine hides. The sampling sites of higher contamination were desks, in both the slaughterhouse and in processing/chilling plants inspected.